Z najnowszych badań archeologicznych nad założeniami obronnymi dawnego województwa skierniewickiego - Kosiorek, Andrzej (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
The article is devoted to the research on Mediaeval and contemporary defensive objects located on the rivers Rawka and Lupia. Strongholds and mounds (remains of manor houses) from the Skierniewice region have their origin between the second half of the 12th century and the first half of the 17th century. The article presents the results of examinations conducted at the sites in Rzeczkowo (Skierniewice commune); Kurzeszyn Stary (Rawa Mazowiecka commune); Stara Rawa (Nowy Kawęrzyn commune); Dębowa Góra and Żelazna (Skierniewice commune). Excavations were carried out on initiative of the Provincial Conservator of Monuments in Skierniewice, Zbigniew Lechowicz (with an exception of the stronghold in Stara Rawa which was examined by Jerzy Gula). Archaeological sources gained during excavation works enabled reconstruction of the process of shaping ancestral settlement in Mazovia (Mazowsze) in the 12th-14th centuries and intensification of farming activity of knights and noblemen in the 15th century. According to the authors, field works and examination of described objects should be continued for more detailed publication.